2017
DOI: 10.3389/fphar.2017.00679
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Testis Toxicity Induced by Chronic Exposure to Mequindox

Abstract: Mequindox (MEQ) is a synthetic antimicrobial agent widely used in China since the 1980s. Although the toxicity of MEQ is well recognized, its testis toxicity has not been adequately investigated. In the present study, we provide evidence that MEQ triggers oxidative stress, mitochondrion dysfunction and spermatogenesis deficiency in mice after exposure to MEQ (0, 25, 55, and 110 mg/kg in the diet) for up to 18 months. The genotoxicity and adrenal toxicity may contribute to sperm abnormalities caused by MEQ. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Mequindox, a relative new compound in QdNOs, is widely applied in livestock owing to its strong inhibitory activities against microbes in China ( Liu et al, 2012 ; Wu et al, 2012 ; Li et al, 2014 ; Wang et al, 2016b ). Early findings have demonstrated that adrenal toxicity ( Huang et al, 2009 ), testicular toxicity ( Ihsan et al, 2011 ; Liu et al, 2017c , b ), kidney and liver toxicity ( Huang et al, 2010a ; Liu et al, 2017d ) induced by MEQ in vivo . CBX ( World Health Organization [WHO], 1991a ) and OLA ( World Health Organization [WHO], 1991b ), structural analogs of MEQ, were prohibited in food-producing animals due to its potential mutagenic and carcinogenic effects ( Wu et al, 2007 ; Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mequindox, a relative new compound in QdNOs, is widely applied in livestock owing to its strong inhibitory activities against microbes in China ( Liu et al, 2012 ; Wu et al, 2012 ; Li et al, 2014 ; Wang et al, 2016b ). Early findings have demonstrated that adrenal toxicity ( Huang et al, 2009 ), testicular toxicity ( Ihsan et al, 2011 ; Liu et al, 2017c , b ), kidney and liver toxicity ( Huang et al, 2010a ; Liu et al, 2017d ) induced by MEQ in vivo . CBX ( World Health Organization [WHO], 1991a ) and OLA ( World Health Organization [WHO], 1991b ), structural analogs of MEQ, were prohibited in food-producing animals due to its potential mutagenic and carcinogenic effects ( Wu et al, 2007 ; Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…MEQ induced oxidative stress in liver and kidney in rats after exposure to MEQ (25, 55, 110, and 275 mg/kg) for 180 days ( Huang et al, 2009 , 2010b ). Recently, we also found that MEQ produced toxicity in liver and testis of KM mice at a dose level of 25, 55, and 110 mg/kg diet ( Liu et al, 2017b , c , d ).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Chronic studies of MEQ on rats induced adrenal toxicity ( Huang et al, 2009 ), invoked oxidative stress in liver and kidney ( Huang et al, 2010b ), and caused hepatic histological changes ( Ihsan et al, 2010 ). Recent studies revealed that toxicity of liver, kidney, and testis in mice was induced by MEQ at a dose level of 25, 55, and 110 mg/kg diet ( Liu et al, 2017b , c , d , 2018a ). In genotoxicity tests, MEQ exhibited a strong genotoxic potential to bacteria, mammalian cells in vitro and in vivo and its mutagenicity is slightly higher than CBX ( Ihsan et al, 2013a ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the toxicity to liver ( Liu et al, 2017 ) and testis ( Liu et al, 2017a , b ) were caused by MEQ in Kunming mice, while the kidney toxicity of MEQ in Kunming mice remains poor understood. Thus, the Kunming mice were chosen in this study.…”
Section: Methodsmentioning
confidence: 99%